ANALISIS DISTRIBUSI TEMPERATUR PERMUKAAN TANAH WILAYAH POTENSI PANAS BUMI MENGGUNAKAN TEKNIK PENGINDERAAN JAUH DI GUNUNG LAMONGAN, TIRIS-PROBOLINGGO, JAWA TIMUR - Nur Faridah, Sri Ana; Krisbiantoro, Agus (BERKALA FISIKA, 2014)
Geothermal is a good alternative energy for this country. Are on track the ring of fire that able to make Indonesia has big and plenitude geothermal reserve. There are 11 regions in East Java that predict as geothermal prospect’s regions. Mount Lamongan’s region, Tiris- Probolinggo, East Java is the object of this research. The existence of geothermal in a region can identify with the surface manifestation, such as hot spring, fumaroles, geyser, hot mud, etc. Remote sensing technique can be use for identifying the indication of geothermal potency from the land surface temperature in the research region. Data analysis from Landsat 7 ETM+ path/row 118/65 (in 6 band thermal) in 2010-2013, it will describe of land surface temperature of geothermal prospect in study area. The result of land surface temperature showed that there is a heat distribution in the study area where the temperature ranges from 37oC up to 67oC, and it is alleged indication of geothermal. Therefore, it is interesting to study as the first step to explore geothermal safe and easy. Keywords: geothermal potency, land surface temperature, remote sensing, Landsat 7 ETM+ imagery, mount Lamongan.